MARKETING STRATEGY OF BANANA BUSINESS IN PANGKAJENE AND ISLANDS REGENCY - Jufri, Muhammad; Tripana, Hendrawan; Syam, Agus; Asmayanti, Asmayanti; Sudarmi, Sudarmi (Jurnal Ekonomi Kreatif dan Manajemen Bisnis Digital, 2024)
The primary objective of this research is to comprehensively identify and recommend an effective business marketing strategy tailored to enhance product sales through digital platforms for Juragan Banana, a business located in Pangkep Regency. The research methodology employed is descriptive qualitative research, encompassing data collection techniques such as observation, interviews, and documentation of the research subject. The gathered data is subsequently subjected to a thorough analysis utilizing the SWOT (Strengths, Weaknesses, Opportunities, Threats) analysis framework. Upon delving into the outcomes of the study, it becomes evident that Juragan Banana Business has strategically positioned itself in the Aggressive quadrant through the application of a growth-oriented strategy. This positioning is deemed highly favorable, as indicated by the SWOT analysis. The business has leveraged its strengths to overcome weaknesses, seize opportunities, and mitigate potential threats. The execution of a Marketing Strategy has played a pivotal role in aligning with the growth-oriented strategy, creating a conducive environment for the business to thrive. By continuing to implement and fine-tune this strategic approach, Juragan Banana Business is well-positioned to not only sustain its current growth trajectory but also to expand its reach, fostering an environment conducive to achieving maximum progress. The growth-oriented strategy, coupled with the effective implementation of marketing strategies, provides a solid foundation for ongoing success and development within the dynamic landscape of digital platforms and sales optimization.